الإعذار بخفاء الحكم وتطبيقاته في فقه الشافعية - عبدالرحمن، محمد حسن أبو العز (دار الافتاء المصرية, 2023)
This research employs a descriptive-analytical approach to shed light on an important though understudied principle that has not received sufficient attention, namely offering a justification to someone who was ignorant of the law due to an unapparent ruling. This principle, which demonstrates a manifestation of religious facilitation and difficulty alleviation, is derived from the branches of legal rulings found in the books of Shafi'i scholars.
Keywords: المذهب الشافعي -- القرآن الكريم -- تفسير القرآن -- الأحكام الشرعية -- المعاملات المالية